2007
DOI: 10.1302/0301-620x.89b3.18199
|View full text |Cite
|
Sign up to set email alerts
|

Monteggia fractures in adults

Abstract: The objective of this retrospective study was to correlate the Bado and Jupiter classifications with long-term results after operative treatment of Monteggia fractures in adults and to determine prognostic factors for functional outcome. Of 63 adult patients who sustained a Monteggia fracture in a ten-year period, 47 were available for follow-up after a mean time of 8.4 years (5 to 14). According to the Broberg and Morrey elbow scale, 22 patients (47%) had excellent, 12 (26%) good, nine (19%) fair and four (8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(44 citation statements)
references
References 24 publications
3
38
1
2
Order By: Relevance
“…The displacement by muscle forces across the fracture site and associated ligamentous injury has been shown to be a source of significant morbidity in the past, especially before the routine use of contoured compression plates for treatment [10, 11]. Bado type II and injuries with associated radial head and coronoid fractures have historically portended poor clinical outcomes [3]. Potential complications of Monteggia fractures include persistent dislocation of the radial head, elbow stiffness, forearm synostosis, nerve palsy, and residual forearm deformity [12].…”
Section: Discussionmentioning
confidence: 99%
“…The displacement by muscle forces across the fracture site and associated ligamentous injury has been shown to be a source of significant morbidity in the past, especially before the routine use of contoured compression plates for treatment [10, 11]. Bado type II and injuries with associated radial head and coronoid fractures have historically portended poor clinical outcomes [3]. Potential complications of Monteggia fractures include persistent dislocation of the radial head, elbow stiffness, forearm synostosis, nerve palsy, and residual forearm deformity [12].…”
Section: Discussionmentioning
confidence: 99%
“…Several other authors also observed the predominance of Bado type II fractures in adults [8,16,22,23,29], while in children and in cases of high-energy trauma, Bado type I injuries are more common [28,32]. Bado type I lesions show excellent or good functional outcomes in most cases, probably due to a low incidence of concomitant fractures of the radial head or the coronoid process [16,28,32]. In contrast, Bado type II lesions are reported to show significantly poorer outcomes [16,26,28].…”
Section: Discussionmentioning
confidence: 93%
“…Bado type I lesions show excellent or good functional outcomes in most cases, probably due to a low incidence of concomitant fractures of the radial head or the coronoid process [16,28,32]. In contrast, Bado type II lesions are reported to show significantly poorer outcomes [16,26,28]. Fractures of the radial head or the coronoid process have been reported to correlate with poor functional outcome scores and occur more frequently in older patients with associated bone weakness [16,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,64 These fractures, unlike proximal radial shaft fractures, are thought to confer a worse prognosis. 40 Proximal ulnar fractures occurring in association with a fractured radial head should be fixed to provide a stable posterior column. Because comminuted radial head fractures are usually secondary to a high-energy injury, associated ulnar fractures tend to have multiple fragments rather than be simply transverse or oblique.…”
Section: Proximal Ulnar Fracturesmentioning
confidence: 99%